2005
DOI: 10.1111/j.1399-0039.2005.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the functional NFKB1 promoter polymorphism in rheumatoid arthritis and systemic lupus erythematosus

Abstract: Nuclear factor (NF)-kappaB plays an important role in inflammatory diseases such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). A functional insertion/deletion polymorphism (-94ins/delATTG) has been identified in the promoter of the NFKB1 gene. In addition, a polymorphic dinucleotide repeat (CA) has been identified in proximity to the coding region of the human NFKB1 gene. The aim of the present study was to investigate the influence of both the -94ins/delATTG and the (CA) microsatellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
(28 reference statements)
1
24
0
1
Order By: Relevance
“…[16][17][18] However, one study reported an epistatic interaction between NFKB1 and Fc receptor-like 3 (FCRL3) gene in Spanish-Caucasian patients with rheumatoid arthritis. 19 Interestingly, FCRL3 has been recently associated with susceptibility to GD.…”
Section: Nfkb1 Promoter Polymorphism In Graves' Disease a Kurylowicz mentioning
confidence: 99%
“…[16][17][18] However, one study reported an epistatic interaction between NFKB1 and Fc receptor-like 3 (FCRL3) gene in Spanish-Caucasian patients with rheumatoid arthritis. 19 Interestingly, FCRL3 has been recently associated with susceptibility to GD.…”
Section: Nfkb1 Promoter Polymorphism In Graves' Disease a Kurylowicz mentioning
confidence: 99%
“…In Rheumatoid Arthritis, both in vitro and in vivo studies indicate an important role of NF-jB signalling in the development and progress of the disease [13]. However, case-control studies performed in different populations failed to replicate the association of the NFKB1 polymorphism with rheumatoid arthritis (AR), systemic lupus erythematosus (SLE) and ankylosing spondylitis (AS) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…According to Orozco et al NFKB1 SNP rs28362491 did not play a role in the development of RA and SLE in Spain population including 272 RA patients, 181 SLE patients, and 264 healthy individuals [55]. However, homozygosity of del allele of rs28362491 has an increased risk of RA in Spain population [73].…”
Section: Nfkb1 and Parp-1 Polymorphisms In Relation To Inflammatory Dmentioning
confidence: 99%
“…There is a growing amount of evidence that variations within the NFKB1 and NFKBIA genes potentially influence the function of NFKB during development of common inflammatory and autoimmune diseases both in health and various disease conditions such as ulcerative colitis [8,53], Crohn's disease [54], RA, SLE [55], psoriatic arthritis [56], giant cell arteritis [57], Celiac disease [58], Type 1 diabetes [59], oral submucous fibrosis [60], and oral squamous cell carcinoma [60].…”
Section: The Role Of Nfkb1 and Parp-1 Inflammatory Diseasementioning
confidence: 99%